Pembelajaran TASTAFI (Tasawuf, Tauhid, dan Fikih) dan Pembinaan Karakter Islami Kaum Ibu di Majelis Taklim Berkah Sekumpul - Audia, Quin Tara; Herni, Zulfiana (Cetta: Jurnal Ilmu Pendidikan, 2024)
This study aims to investigate the role of TASTAFI (Tasawuf, Tauhid, and Fikih) learning and Islamic character building in the Ta'lim Berkah Sekumpul assembly for mothers in Lubuk Bayas Village. The background of this research is the importance of strengthening the understanding of Islam and Islamic character building through non-formal education in the community. Qualitative research methods were used to analyze the impact of this holistic learning on participants, especially mothers. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using a descriptive qualitative approach. mThe results show that majelis Ta'lim Berkah Sekumpul uses an inclusive and adaptive approach that is able to respond to differences in educational backgrounds and religious understanding among participants. This enabled the women to internalize Islamic values more effectively. Participants showed improvement in their religious understanding and application of Islamic teachings in daily life. In addition, Islamic character building through majelis Ta'lim activities also significantly contributes to strengthening the moral and spiritual foundation of participants, which has a positive impact on family life and the surrounding community. The conclusion of this study is that TASTAFI learning and Islamic character building at the Berkah Sekumpul Ta'lim assembly make an important contribution to strengthening the morality and spirituality of the Muslim community in Lubuk Bayas Village. The majelis Ta'lim's inclusive and adaptive approach is effective in building deeper religious understanding and strong character building, especially among mothers. This finding confirms the strategic role of majelis ta'lim in developing human resources with Islamic character at the community level.